Failure analysis on tube arm cylinder hydraulic excavator - Pratama, Fikri Wahyu; Siradj, Eddy Sumarno; Rahman, Okky Helja Octora Syahida (Universitas Negeri Padang, 2022)
The Failure on tube rod arm cylinder hydraulic excavator caused to lose production and processing time on mining site. Investigation included visual inspection, chemical analysis, metallography analyze, and microhardness test. Tube material used high silicon material type while the standard used ST52 carbon steel type. The tube was broken and crack to several pieces. The chemical composition of the tube has different in sulfur and silicon content. From hardness test with micro hardness method, sample tube broken has lower hardness compared to standard hardness. Metallography analysis obtained the phase of tube has same phase with standard which is ferrite and pearlite phase but has different grain size. Based on this study, it can be resumed failure on tube is because impurities and different specification on raw material.